THE EFFECT OF PERSONAL EXPERIENCES STRATEGY ON STUDENTS’ ACHIEVEMENT IN WRITING NARRATIVE TEXTS - Anisya Hardiant Daulay; Sumarsih Sumarsih; Masitowarni Siregar (Universitas Negeri Medan, 2015)
This study attempts to discover the effect of applying Personal Experiences Strategy on students’ achievement in writing narrative text. It was conducted by using experimental research design. The population of this research was the tenth (X) grade students of SMA N 6 Padangsidimpuan which consists of 10 parallel classes with the total number of students is 64. The samples of this research were taken by random sampling through lottery technique. The result was class X1 consisted of 32 students became the experimental group and class X2 consisted of 32 students became the control group. The experimental group was taught by Personal Experiences Strategy while the control group was taught by using Big group work strategy. The instrument was used to collect the data was writing narrative text. After the data were analyzed, it was found that the value of t-observed was 4.25 with the degree of freedom (df) = 62 at the level significance 0.05. it means that t-observed was higher than t-table (4.25 > 1.997. The result of this study showed that teaching narrative text by using personal experiences strategy was higher than that by big group work. Keywords : Using Personal Experiences Strategy. Writing Narrative Text.